Examining the challenges Chinese university students encounter in upholding academic integrity in research work - Chen, Lin; Saharuddin, Norzihani; Muhamad, Mohd Mokhtar (Routledge, 2025)
This study aims to explore the challenges faced by Chinese university students in maintaining academic integrity in their research, focusing on a sample of 150 students from various higher education institutions. Using a mixed-methods approach, the study investigates the factors influencing academic integrity and the methods students employ to uphold ethical standards in their work. Data were collected through surveys and interviews and analysed using qualitative content analysis. The findings reveal several challenges, including insufficient awareness of plagiarism, a lack of research ethics knowledge, and limited institutional support. Coping strategies identified include increased use of plagiarism detection tools, awareness-raising on academic integrity, and enhanced mentoring support from faculty. The study provides recommendations for improving academic integrity education and the implementation of more robust plagiarism prevention measures.